Ativação in situ de oxidantes mediada por irradiação UVC: um estudo do tipo e concentração de oxidantes em distintas matrizes aquosas - Pinto, Gabriel Antonio (Universidade Federal de São Carlos, 2025)
As a consequence of the increasing production and use of synthetic organic compounds, a growing detection of these pollutants has been observed in water bodies. Depending on their concentration and exposure, these substances may pose risks to human health and aquatic life. One of the main factors contributing to their presence is the inefficiency of conventional treatment methods, which are not effective in removing such compounds. In this context, the present study investigated the efficiency of UVC-based advanced oxidation processes for the simultaneous removal of four micropollutants: ciprofloxacin (CIP), enrofloxacin (ENRO), norfloxacin (NOR), and imidacloprid (IMD). Two systems were evaluated: UVC/H2O2, as a source of hydroxyl radicals (HO•), and UVC/S2O82–, as a combined source of sulfate (SO4•–) and HO• radicals. For the three fluoroquinolones, a concentration of 500 μmol L–1 of H2O2 provided the best results in terms of oxidation rate and oxidant consumption. In the case of the UVC/S2O82– system, its performance was similar across all tested concentrations, allowing the same value to be used for comparison. Overall, the UVC/S2O82– process showed superior performance compared to UVC/H2O2 in the oxidation rate of fluoroquinolones. On the other hand, the oxidation of IMD was not significantly affected by the different oxidant concentrations, resulting in similar oxidation rates for both processes and being primarily dependent on the photochemical process. The efficiency of both systems was also evaluated in different aqueous matrices: deionized water, tap water, and simulated effluent from a biological wastewater treatment plant. In the UVC/H2O2 process, a slight inhibition in the degradation of micropollutants was observed in the more complex matrices, especially in the simulated wastewater, likely due to light attenuation and the consequent decrease in oxidant activation. In contrast, in the UVC/S2O82– system, both the oxidation rate and oxidant consumption remained similar across all matrices, demonstrating greater robustness and versatility in the presence of matrix interferences. Toxicity assays using Escherichia coli indicated that although UVC irradiation alone achieved a good oxidation rate, it was not effective in removing the residual toxicity of fluoroquinolones. In contrast, the UVC/H2O2 and UVC/S2O82– processes proved effective in reducing toxicity, reinforcing their potential for application in advanced treatment of effluents containing emerging contaminants. Finally, process cost was shown to be largely dependent on the lamp power and the type of pollutant targeted for oxidation.
In situ activation of oxidants mediated by UVC irradiation: a study of the type and concentration of oxidants in different aqueous matrices
Keywords: Processos oxidativos avançados; Contaminantes emergentes; Radicais hidroxila; Radicais sulfato; Advanced oxidation processes; Emerging contaminants; Hydroxyl radicals; Sulfate radicals; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA